Correlation study between serum neuro-specific enolase and gastric and colorectal cancers. Issue 16 (April 2020) - Luo, Hai; Shen, Kexin; Sun, Hongyan; Li, Ruiqi; Wang, Zeming; Xie, Zhongshi
Abstract : Abstract: This study investigated the diagnostic value of preoperative serum neuro-specific enolase (NSE) in gastric cancer (GC) and colorectal cancer (CRC), and the diagnostic viability of combined serum NSE, carcinoembryonic antigen (CEA), cancer antigen (CA)19-9, and CA242. Patients with GC and CRC, and a healthy control group (n = 666 and 266, respectively) were compared with regard to NSE, CEA, CA19-9, and CA242 serum levels. NSE was analyzed for associations with clinicopathological parameters. To estimate the diagnostic potential of NSE, a receiver operating characteristic curve was constructed and the area under the curve (AUCs) was calculated for different patient subgroups. The median serum NSE level of the tumor group (20.925 ng/mL) was significantly higher than that of the control (15.190 ng/mL). Serum NSE was associated with pathological tumor-node-metastasis staging, lymph node metastasis, distant metastasis, vascular invasion, and nerve infiltration. The area under the receiver operating characteristic curve (AUC) for NSE in GC and CRC (0.769) was higher than for the other 3 markers (0.571–0.680). The AUC of the combined markers was higher than for any of the markers individually (0.778–0.810). The AUC for NSE alone suggests it may be an independent tumor marker, and useful for diagnosis of GC and CRC. However, the AUC for combined NSE, CEA, CA19-9, and CA242 was higher and thus potentially more diagnostic value.